Deficiency of d-Erythroascorbic Acid Attenuates Hyphal Growth and Virulence of Candida albicans - Huh, Won-Ki (American Society for Microbiology, 2001)
In some lower eukaryotes, d-erythroascorbic acid, a five-carbon analog of l-ascorbic acid, is present instead of l-ascorbic acid. We have cloned ALO1, the gene encoding d-arabinono-1,4-lactone oxidase, which catalyzes the final step of d-erythroascorbic acid biosynthesis in Candida albicans. The ALO1 gene contained a continuous open reading frame of 1,671 bp that encodes a polypeptide consisting of 557 amino acids with a calculated molecular mass of 63,428 Da. To investigate the functional roles of d-erythroascorbic acid in C. albicans, we disrupted or overexpressed the ALO1 gene. In the alo1/alo1 null mutants, the activity of d-arabinono-1,4-lactone oxidase was completely lost and d-erythroascorbic acid could not be detected. When ALO1 on a multicopy plasmid was transformed in C. albicans, the enzyme activity and the intracellular d-erythroascorbic acid level were increased up to 3.4-fold and 4.0-fold, respectively. The alo1/alo1 null mutants of C. albicans showed increased sensitivity towards oxidative stress. Overexpression of ALO1 made the cells more resistant to the same stress. The alo1/alo1 mutants showed defective hyphal growth and attenuated virulence. Taken together, our results suggest that d-erythroascorbic acid functions as an important antioxidant and can be considered one of the virulence factors enhancing the pathogenicity of C. albicans.